2021
DOI: 10.3390/ijerph18094428
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions Used in Instruments for QALY Calculation: A Systematic Review

Abstract: Economic assessment is of utmost importance in the healthcare decision-making process. The quality-adjusted life-year (QALY) concept provides a rare opportunity to combine two crucial aspects of health, i.e., mortality and morbidity, into a single index to perform cost-utility comparison. Today, many tools are available to measure morbidity in terms of health-related quality of life (HRQoL) and a large literature describes how to use them. Knowing their characteristics and development process is a key point fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 71 publications
1
22
0
5
Order By: Relevance
“…The instruments with the best coverage of the dimensions of the evaluation framework lack a preference-based scoring algorithm, at present. In line with the study of Touré and colleagues [ 58 ], it was found that all identified preference-based instruments, which were all generic, cover the dimension “Physical health”, but generally lack coverage of mental health related (sub)dimensions. Of the five instruments that were found to have a preference-based scoring algorithm, the AQoL-8D had the most overlap with the framework of Connell and colleagues [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 77%
“…The instruments with the best coverage of the dimensions of the evaluation framework lack a preference-based scoring algorithm, at present. In line with the study of Touré and colleagues [ 58 ], it was found that all identified preference-based instruments, which were all generic, cover the dimension “Physical health”, but generally lack coverage of mental health related (sub)dimensions. Of the five instruments that were found to have a preference-based scoring algorithm, the AQoL-8D had the most overlap with the framework of Connell and colleagues [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, measurements were based on self-reports and, in the case of cost data, this could have resulted in recall bias and led to over- or underestimation of total costs. Third, the use of a measure that is more sensitive to changes in healthy populations and that does not have a tendency for ceiling effects (such as the SF-6D or the CORE-6D; 49;51) could be beneficial to differentiate between high scores of the healthy utility range. Fourth, consistent with other studies of web-based interventions (52), dropout rates were relatively high, particularly at the last assessment point.…”
Section: Discussionmentioning
confidence: 99%
“…In each round, using specific questions, points of view, suggestions, and misunderstandings of respondents were collected anonymously (all respondents did not know the individual opinions of other participants but were informed of the global distribution of responses). In each round, a revised version of the questionnaire, based on the respondents' observations and suggestions in the previous round, was created—except for the first round—where the dimensions proposed were derived from the study by Touré et al ( 7 ), which is a systematic review of the dimensions covered by HRQoL instruments and the different steps necessary for the creation of those instruments for QALY calculation. Further details on the selected studies and the dimensions can be found elsewhere ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, generic instruments are adapted for all types of health profiles to allow for the comparison between patients with different diseases ( 6 ). However, many differences may be perceived among the generic instruments available regarding their composition, where dimensions related to physical aspects of health are depicted more often than dimensions related to mental or social aspects ( 7 ). The general observation is that almost all generic instruments contain one or more dimensions related to physical aspects (e.g., disability, discomfort/pain) at the expense of other dimensions, such as mental/cognitive function, wellbeing/happiness, or sadness/depression ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation